The Efficacy of Acupuncture for the Treatment of Cervical Vertigo: A Systematic Review and Meta-Analysis. (9th May 2017) - Hou, Zhuanzhuan; Xu, Shibing; Li, Qinglin; Cai, Libing; Wu, Weigang; Yu, Huida; Chen, Huade
Abstract : Objective . This study aims to evaluate the efficacy and safety of acupuncture for the treatment of cervical vertigo (CV). Methods . Randomized controlled trials (RCTs) regarding effectiveness of acupuncture for treating CV were searched in 7 comprehensive databases prior to April 2016. The data analysis was performed by using RevMan version 5.3. Results . A total of 10 studies with 914 participants were included. Results showed that acupuncture was more effective than conventional medicine therapy (CMT) in effectiveness, improvement rate of vertigo and headache, and increased average blood flow velocity of vertebral-basilar artery. In the subgroup analysis, the results did not change in different acupuncture methods and drug categories substantially. Sensitivity analysis demonstrated that the results of this meta-analysis were stable. Meanwhile, the long-term safety of acupuncture for CV still remains uncertain. GRADE analysis indicated that the quality of evidence for all outcomes was from very low to low which limited the value of the meta-analysis. Conclusion . Based on the systematic review, acupuncture appeared to be a promising therapeutic approach for CV based on low or very low quality of evidence. However, large-scale and high-quality trials are required to provide stronger evidence for the conclusion.